Visual Product Identification for Blind People - Prof. G. S .Mate, Harshada Godambe, Madhuri Maske, Akash Gomare (International Journal of Advanced Science and Technology, 2020)
This project is developed to make the life of blind people easy. This is a camera based system to scan the product behind the image and read the description of the product with the help of Id stored in the product. This is very beneficial in case of finding out the description of packaged goods to the blind people and thus helping them in deciding to purchase a product or not especially which are packaged. This is because it becomes very difficult for the blind people to distinguish between the packaged goods. In order to use this system, all the user needs to do is capture the image on the product in the device which then resolves the product which means it scans the image to find out the Id stored. Thus this application really benefits blind and visually impaired people and thus making their work of identifying products easy. This is very easy to use and affordable as it requires a scanner to scan the product and a camera phone to take the picture of the image containing the product. This is now easy to implement as most of the devices today have the required resolution in order to scan the product to identify the Id stored in it and read out the product description. This project can be implemented in any shopping mall, supermarket, Book stores, Medical stores etc